# 10m-4(3m+7)+6m=0

## Simple and best practice solution for 10m-4(3m+7)+6m=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 10m-4(3m+7)+6m=0 equation:

Simplifying
10m + -4(3m + 7) + 6m = 0

Reorder the terms:
10m + -4(7 + 3m) + 6m = 0
10m + (7 * -4 + 3m * -4) + 6m = 0
10m + (-28 + -12m) + 6m = 0

Reorder the terms:
-28 + 10m + -12m + 6m = 0

Combine like terms: 10m + -12m = -2m
-28 + -2m + 6m = 0

Combine like terms: -2m + 6m = 4m
-28 + 4m = 0

Solving
-28 + 4m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '28' to each side of the equation.
-28 + 28 + 4m = 0 + 28

Combine like terms: -28 + 28 = 0
0 + 4m = 0 + 28
4m = 0 + 28

Combine like terms: 0 + 28 = 28
4m = 28

Divide each side by '4'.
m = 7

Simplifying
m = 7`